Polymorphisms in the cytochrome P-450 (CYP) 1A1 and 17 genes are not associated with acne vulgaris in the Polish population - Sobjanek, Michał; Zabłotna, Monika; Dobosz-Kawałko, Magdalena; Michajłowski, Igor; Mędrzycka-Dąbrowska, Wioletta; Nowicki, Roman; Sokołowska-Wojdyło, Małgorzata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : The pathogenesis of acne is complex, multifactorial and not well understood. The genetic background of this dermatosis is well documented. Aim : To assess the frequency of –34 T>C single nucleotide polymorphism in the promoter of the CYP17 gene as well as m1 (+6,235 T>C) and m 2 (+4,889 A>G) mutation in the coding region CYP1A1 gene acne patients from the Northern Polish population. Material and methods : The study included 115 acne patients and 94 healthy controls (aged over 20) without acne in anamnesis. The CYP1A1 polymorphism was analyzed by polymerase chain reaction (PCR). The restriction fragment length polymorphism (RFLP) was used to analyze m1 mutation and allele-specific PCR in the case of m 2 mutation. The CYP17 polymorphism was analyzed by RFLP. The results were evaluated by the Pearson’s c2 test. Results: There were no statistically significant associations between allele and genotype frequencies between the acne and the control group. Conclusions : We did not confirm the role of the CYP1A1 and CYP17 gene as predictor factors for acne development in the Polish population.